Influencing factors affecting environmental attitudes (Training and Practice : Journal of Educational Sciences, 2018)
In the past decade, environmental education received ever increasing attention in the Hungarian educational system. In addition to the diverse educational methods used in shaping the learners’ appropriate environmental attitude, the Eco-school Network /Ökoiskola/ also plays an important role. The arsenal of methods used in and out of class that can be used to raise environmental awareness is continuously growing. The question is whether the various conditions do, in fact, contribute to the development of the students’ positive environmental attidutudes. In our investigation we examined influencing factors (school maintainer, year), which, according to our hypothesis, help the shaping of environmental attitude. Our results suggest that the type of the school is not a decisive factor in shaping the environmental attitude of the students examined. There is no change for the better in students’ environmental attitude in higher grades (clasess 9 to 12), either.